Cyclic deformation of TiAl generic microstructures at room and high temperature: Bauschinger effect & strain rate sensitivity. (July 2020) - Serrano, P.; Toualbi, L.; Kanoute, P.; Couret, A.
Abstract: The cyclic deformation of four TiAl common microstructures is studied experimentally at room and high temperature. Multilevel and multirate tests are performed to highlight the microstructure impact on the Bauschinger effect and the strain rate sensitivity. The mechanical behaviors are linked to their corresponding deformation mechanisms. Results can directly be used to develop microstructure-sensitive modeling of the mechanical behaviors of TiAl alloys. Highlights: The cyclic deformation of four TiAl common microstructures is studied. The Bauschinger effect is linked to the microstructure. The transient softening increases with the volume fraction of γ grains. A pronounced kinematic hardening is observed. The strain rate sensitivity increases with the volume fraction of γ grains.